2011
DOI: 10.3109/10903127.2010.534235
|View full text |Cite
|
Sign up to set email alerts
|

An Open, Interoperable, and Scalable Prehospital Information Technology Network Architecture

Abstract: Some of the most intractable challenges in prehospital medicine include response time optimization, inefficiencies at the emergency medical services (EMS)-emergency department (ED) interface, and the ability to correlate field interventions with patient outcomes. Information technology (IT) can address these and other concerns by ensuring that system and patient information is received when and where it is needed, is fully integrated with prior and subsequent patient information, and is securely archived. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…[35] Real-time information exchange may be more difficult for mobile prehospital providers operating in austere settings lacking robust wireless communication infrastructures. [6] Study participants also reported difficulty responding to mandates requiring the adoption of e-PCR systems. Other US health care providers are being encouraged to adopt HIT under federal health policy, most notably from the Health Information Technology for Economic and Clinical Health (HITECH) Act, which provides incentive funding for hospital and ambulatory EHR adoption (with penalties in subsequent years if not adopted).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[35] Real-time information exchange may be more difficult for mobile prehospital providers operating in austere settings lacking robust wireless communication infrastructures. [6] Study participants also reported difficulty responding to mandates requiring the adoption of e-PCR systems. Other US health care providers are being encouraged to adopt HIT under federal health policy, most notably from the Health Information Technology for Economic and Clinical Health (HITECH) Act, which provides incentive funding for hospital and ambulatory EHR adoption (with penalties in subsequent years if not adopted).…”
Section: Discussionmentioning
confidence: 99%
“…[6], [9] Our research, combined with a future comprehensive, quantitative survey of US EMS agency e-PCR system capacity as well as barriers and strategies to e-PCR system adoption, implementation and use, could better characterize the unique needs of EMS agencies. Federal support for additional e-PCR systems research could help determine the impact of e-PCR systems on ambulance call times and identify efficient e-PCR system workflows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic prehospital PCRs are now widely available and commonly used in many emergency medical services (EMS) systems. Despite this change, there are still barriers to timely and accurate information delivery 9. Most modern electronic prehospital PCR systems use an internet-based network and/or telefacsimile (FAX) transmission to deliver the prehospital information to the receiving facility.…”
Section: Introductionmentioning
confidence: 99%